PENGARUH PENYULUHAN TENTANG JAJANAN SEHAT TERHADAP SIKAP ANAK SD KELAS IV DAN V DALAM KONSUMSI JAJANAN DI SDN V AJUNG KALISAT KABUPATEN JEMBER - Anwarah Andriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
School snacks today need to be a concern of the community, especially parents, educators, and school managers. School food and snacks are very at risk from biological or chemical contaminants which are detrimental to health, both short and long term. This study is a pre-experimental one group pretest - post test that aims to determine the effect of counseling about healthy snacks on the attitude of elementary school children in the consumption of snacks at SDN V Ajung Kalisat, Jember Regency. The population in this study was 60 respondents with a sample of 52 respondents. The sampling technique used is simple random sampling. The results of this study indicate that the attitude of elementary school children in the consumption of snacks before getting counseling is negative as many as 27 people (51.9%) after receiving positive counseling as many as 40 people (63.73%). Based on the Wilcoxon test analyzed using SPSS, the significance value (Asymp. Sig) obtained between attitude before and after counseling was 0.008 <0.05, meaning that ho was rejected and ha was accepted, so that there was an effect of counseling about healthy snacks on the attitudes of elementary school children grade IV and V in Consumption of snacks in SDN V Ajung Kalisat Jember Regency. The conclusion of this research is that counseling has been proven to be effective in changing students' attitudes towards consuming healthy snacks, so the more often information / counseling is provided, the better the attitude is formed. Given the importance of counseling on the consumption of snacks, efforts to improve the provision of information by the school to elementary students is very important so that the risk of disease can be reduced